2016
DOI: 10.1590/s1806-37562016000000226
|View full text |Cite
|
Sign up to set email alerts
|

Is there a rationale for pulmonary rehabilitation following successful chemotherapy for tuberculosis?

Abstract: The role of tuberculosis as a public health care priority and the availability of diagnostic tools to evaluate functional status (spirometry, plethysmography, and DLCO determination), arterial blood gases, capacity to perform exercise, lesions (chest X-ray and CT), and quality of life justify the effort to consider what needs to be done when patients have completed their treatment. To our knowledge, no review has ever evaluated this topic in a comprehensive manner. Our objective was to review the available evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 47 publications
0
42
0
8
Order By: Relevance
“…Cigarette smoking is a risk factor for pulmonary infections, as well as a co-factor contributing to rapid lung function deterioration, reduced exercise tolerance, and impaired QoL (Muñoz-Torrico et al, 2016;Spruit, 2014;Spruit et al, 2013). A number of studies have demonstrated a reduction in frequency and severity of exacerbations in individuals with established chronic lung disease (Willemse et al, 2004;Au et al, 2009).…”
Section: Prevention and Vaccinationmentioning
confidence: 99%
“…Cigarette smoking is a risk factor for pulmonary infections, as well as a co-factor contributing to rapid lung function deterioration, reduced exercise tolerance, and impaired QoL (Muñoz-Torrico et al, 2016;Spruit, 2014;Spruit et al, 2013). A number of studies have demonstrated a reduction in frequency and severity of exacerbations in individuals with established chronic lung disease (Willemse et al, 2004;Au et al, 2009).…”
Section: Prevention and Vaccinationmentioning
confidence: 99%
“…They are likely to benefit most from interventions including smoking cessation, patient education for self-management, pulmonary rehabilitation and bronchodilator therapy. [9,28] The tremendous expense and disability associated with chronic lung diseases in North America and Europe has important implications for the future of low resource countries like Uganda. [29] Even though international guidance is lacking, Uganda has very recently included the issue of post-TB lung disorders into its national TB programme guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A baseline examination with functional evaluation can be performed safely when the patient is smear and culture negative (on at least two samples two weeks apart) and is undergoing effective treatment; otherwise, infection control measures are necessary [13]. As the patient might need a different approach when resting and when making exercise (e.g., walking), a careful evaluation should be ideally performed both at rest and under exercise conditions [43,44].…”
Section: Post-tb Treatment Functional Evaluationmentioning
confidence: 99%